Survey of Cyber security approaches for Attack Detection and Prevention - et. al., MalathiEswaran, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the world of modern technology many devices are frequently handled by the people via network. Since the network has been utilized in communication across the world and also in data sharing, there may be a chance of cyber-attacks and intruding into the personal data of the user. This survey provides a witness in large amount of cyber-attacks widespread in the recent times. The issue also deals with the system under use and with the storage devices concerned. Inorder to manage large amount of data, cloud computing plays a vital role in managing the data and also prevents data from intruders. Many intrusion detection systems help in detecting anomalies, that caused by various cyber-attacks. This proposed survey focuses on types of attacks and also the methodology involved in detecting such type of attacks.